ASSET AND LIABILITY MANAGEMENT STRATEGY TO IMPROVE PROFITABILITY OF ISLAMIC BANKS - Erina Effi Abidah; Ainani Tajriani; Kamila Faradila; Andi Amri (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2024)
This journal research aims to investigate the role of asset and liability management strategies' role in increasing Islamic banks' profitability. In this research, the Literature Review method was used. Where this research contains at least almost 80% of national and international articles and journals and e-books published on various platform providing articles, journals, and e-books at national and international levels that discuss asset and liability management strategies for Sharia banks. Literature Review is a national and international literature search carried out using the Google Scholar database (Knopf, 2006; Sugiyono, 2017). In the context of a changing and complex economy, a deep understanding of how Islamic banks can manage their assets and liabilities is crucial. By focusing on sharia principles, this research will identify strategies that can help sharia banks achieve optimal levels of profitability, while still complying with sharia provisions.